2019
DOI: 10.1183/16000617.0058-2019
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary complications of immune checkpoint inhibitors in patients with nonsmall cell lung cancer

Abstract: Immune checkpoint inhibitor-related pneumonitis (ICI-P) during cancer treatment is rarely observed (<5%). ICI-P is more often observed in patients with nonsmall cell lung cancer (NSCLC) than in those with other cancers. Likewise, it is more common in those receiving programmed cell death (PD)-1/PD-1 ligand inhibitors rather than cytotoxic T-lymphocyte antigen (CTLA)-4 inhibitors alone. The frequency of ICI-P is higher when anti-PD-1 and anti-CTLA-4 are administered concomitantly. Despite the low fatality ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 152 publications
(442 reference statements)
3
85
0
2
Order By: Relevance
“…There have also been case reports of sarcoid-like granulomatous changes associated with ICI, both on CT scan and lung biopsy, but these appear to be more common in patients with melanoma. 55,64 The histologic findings of ICI pneumonitis have not been well described as lung biopsy is not necessary to make the diagnosis of ICI pneumonitis, and biopsy results have been rarely reported in retrospective studies and case reports. Several studies have demonstrated increased lymphocyte proportion on BAL of patients with ICI pneumonitis.…”
Section: Radiographic and Histologic Featuresmentioning
confidence: 99%
“…There have also been case reports of sarcoid-like granulomatous changes associated with ICI, both on CT scan and lung biopsy, but these appear to be more common in patients with melanoma. 55,64 The histologic findings of ICI pneumonitis have not been well described as lung biopsy is not necessary to make the diagnosis of ICI pneumonitis, and biopsy results have been rarely reported in retrospective studies and case reports. Several studies have demonstrated increased lymphocyte proportion on BAL of patients with ICI pneumonitis.…”
Section: Radiographic and Histologic Featuresmentioning
confidence: 99%
“…Also, the pre-existing autoimmune diseases seem not to predict complications [62;63]. The analysis of observations shows that lung fibrosis does not exclude immunotherapy [60]however the course of pulmonary complications may be accomplished by comorbidities. should be selected depending on the kind of ICI related toxicity and its clinical manifestation [79].…”
Section: Skin Toxicitymentioning
confidence: 99%
“…Bilateral distribution and localisation away from lung tumor are often observed[58]. Pleural effusion and mediastinal lymph nodes involvement are rare.The issue of CIP is non-infectious parenchymal inflammation and the COP, AIP or NSIP pattern was confirmed by histological examination, however the data are scanty[59].Sarcoid granulomatosis is a special kind of possible toxicity, however rare, it may involve extrapulmonary organs though[60].The differential diagnosis of new lung infiltrations in ICIs treated patients include tumor progression or pseudoprogression, pneumonia or pneumonitis. Thus, the full microbiological tests and histopathological examination of sputum/material from bronchoscopy is often needed and decisive.…”
mentioning
confidence: 99%
“…According to a recent meta‐analysis of 125 clinical trials involving 20 128 patients, ICI adverse effects, such as severe myocarditis and pneumonitis, are challenging to diagnose and might not be treated promptly, finally affecting patients' survival 73 . Indeed, while in this class of patients, the general risk of bacteria and viral infections is low and not widely investigated in literature, 74 an ICI‐correlated pulmonary toxicity has been previously reported 75 . The overall incidence rate of ICI‐related pneumonitis ranges from 2.5% to 5% with anti‐PD‐1/PD‐L1 monotherapy from 7% to 10% with anti‐CTLA‐4 + anti‐PD‐1 combination therapy 76 .…”
Section: Onco‐dermatologymentioning
confidence: 99%